Luminescent lanthanide (Eu(iii)) cross-linked supramolecular metallo co-polymeric hydrogels: The effect of ligand symmetry - Gunnlaugsson, Thorfinnur; Dee, Garret (My University, 2019)
Two lanthanide luminescent naphthyl-dipicolinic amide (dpa) methacrylate monomers for the synthesis of grafted supramolecular co-polymer gels (hydrogels), and their use as additional crosslinks in robust covalently cross-linked HEMA hydrogels is presented; the results demonstrate the importance of the ligand symmetry for the Eu(iii) emission from the hydrogels
PUBLISHED
cited By 2
Keywords: Organogels; Azobenzene; Gelation